2016
DOI: 10.1007/s11060-016-2307-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival after chemotherapy and stem cell transplant followed by delayed craniospinal irradiation is comparable to upfront craniospinal irradiation in pediatric embryonal brain tumor patients

Abstract: Pediatric embryonal brain tumor patients treated with craniospinal irradiation (CSI) are at risk for adverse effects, with greater severity in younger patients. Here we compare outcomes of CSI vs. high-dose chemotherapy (HD), stem cell transplant (SCT) and delayed CSI in newly diagnosed patients. Two hundred one consecutive patients treated for medulloblastoma (72 %), supratentorial primitive neuroectodermal tumor (sPNET; 18 %) or pineoblastoma (10 %) at two institutions between 1988 and 2014 were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Moreover, survivors are debilitated by significant therapy-associated toxicity, chief among which are neurocognitive deficits, endocrine and growth abnormalities, and an increased risk of secondary malignancy (82)(83)(84). To reduce the burden of treatment-associated toxicity of radiotherapy, high-dose chemotherapy with hematopoietic stem cell rescue and other risk-adapted therapeutic strategies have been used, particularly in young patients (85)(86)(87)(88). However, outcomes remain suboptimal and patients are frequently afflicted with significant therapy-associated sequelae.…”
Section: Number 2 February 2019mentioning
confidence: 99%
“…Moreover, survivors are debilitated by significant therapy-associated toxicity, chief among which are neurocognitive deficits, endocrine and growth abnormalities, and an increased risk of secondary malignancy (82)(83)(84). To reduce the burden of treatment-associated toxicity of radiotherapy, high-dose chemotherapy with hematopoietic stem cell rescue and other risk-adapted therapeutic strategies have been used, particularly in young patients (85)(86)(87)(88). However, outcomes remain suboptimal and patients are frequently afflicted with significant therapy-associated sequelae.…”
Section: Number 2 February 2019mentioning
confidence: 99%
“…Recent studies by Mynarek et al, and Handsford et al similarly found an age of three years to be critically predictive of worse prognosis [ 7 , 64 ]. A 2017 study by Raleigh et al in very young pediatric embryonal brain tumor patients found that post-surgical RT delivered before disease recurrence resulted in better outcomes than did RT at the time of recurrence [ 65 ]. Thus, it is possible that the poor outcomes are driven, at least in part, by the omission or delay of RT in this patient population due to concern for its deleterious toxicities in the very young.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight percent of high-dose CTx patients received neither definitive nor salvage radiotherapy. This cohort, however, included various diagnoses as medulloblastoma, pineoblastoma, and stPNET (Raleigh et al 2017). By contrast, for pineoblastoma use of HD-CTx showed limited impact on survival (Mynarek et al 2017).…”
Section: Systemic Therapymentioning
confidence: 99%